FROM TRANSLATION TO INTERACTION: EVOLUTION OF AI TOOLS IN LANGUAGE TEACHING - UZAKBAEVA, Gulbanu Sabitovna (The Lingua Spectrum, 2025)
Over the last decades, digital technologies have dramatically transformed the landscape of language education. AI-based tools, which initially served primarily translation and error‑correction purposes, have evolved into interactive systems capable of sustaining human‑like dialogue, analyzing learner progress, and personalizing instruction. This paper provides an expanded overview of this evolution by comparing traditional CALL methods, early machine translation tools, and the new generation of conversational agents such as ChatGPT and localized AI systems. Special emphasis is placed on the pedagogical, cultural, and policy implications for multilingual regions such as Uzbekistan, where digitalization is rapidly reshaping educational practices. The study demonstrates that modern AI shifts the focus from translation‑dependent learning toward communicative competence, critical thinking, and authentic interaction.